Analysis of Factors Influencing Soybean Imports from Foreign Countries on Economic Growth in Indonesia - Agustina, Aulia; Hasri, Puspita; Fadillah , Imelia Insyra; Suci , Melda Eka; Nurfarijah, Mega Wahyuni; Ramadan , Gigin; Pratama , Muhamad Ilham; Firmansyah , Ricky (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this research is to find out how big the contribution of soybean imports is to economic growth in Indonesia. The data used in this study is a qualitative analysis method in the form of descriptive statistics to be able to analyze existing data by describing or describing the results of the analysis. The other data collection techniques are carried out by studying literature as literature and references to support conducting research. Based on the results of the analysis, it can be concluded that the factors affecting soybean imports in Indonesia are due to the unbalanced productivity and demand for soybean food. The level of soybean consumption in Indonesia in 2019-2022 has increased by 3.31%, and the level of imports of soybeans in Indonesia has also increased by 4.99%. So it can be seen that the development of soybean imports can continue to increase along with the increase in the level of soybean consumption in society, but this makes Indonesia dependent on imported soybeans which makes the level of development of national production decrease. The rupiah exchange rate with the dollar (US) can cause unstable national soybean prices which can lead to a scarcity of soybean-based foods, farmers and entrepreneurs will strike production and lose money, so that Indonesia will experience a crisis in economic life. Therefore, imports of soybeans from foreign countries have quite a positive effect in helping economic life in Indonesia.